Peningkatan Prestasi Belajar Agama Hindu Berbasis Model Ekspositori Melalui Diskusi Interaktif - Siah, Luh (Journal of Education Action Reseach, 2018)
This research was carried out at SMP Negeri 3 Sawan class VIII A3 whose learning achievement was still low. The purpose of writing class action research is to find out whether the Expository learning model with interactive discussion can improve student learning achievement. The data collection method is a learning achievement test. The data analysis method is descriptive. The results obtained from this study are expository models with interactive discussions can improve student learning achievement. It is evident from the results obtained at first 18% of those who reached the Minimum Completeness Criteria (KKM) after being given the action in the first cycle increased to 34.61% and in the second cycle increased again to 85%. The conclusion obtained from this study is that the expository model with interactive discussion can improve the learning achievement of grade VIII A3 students of SMP Negeri 3 Sawan.